Analysis of bifacial elements from Grotte de la Verpillière I and II (Germolles, France). (15th January 2017) - Frick, Jens Axel; Floss, Harald
Abstract: Bifacial objects are iconic lithic artifacts of Middle Paleolithic assemblages. This paper presents a comparative analysis of the production sequences of bifacial objects from Grottes de la Verpillière I and II (VP I and II) in Germolles, Saône-et-Loire, France. This study shows that despite morphological diversity, a general production sequence exists for all of the bifacial artifacts: phases of backing, bottom-side and top-side configuration and cutting-edge regularization. The study also compares the bifacial assemblages from modern excavations in intact sediments (VP II), mixed sedimentological units (VP I and II), the backdirt of old excavations (VP I) and museum collections from prior excavations and surface collections (VP I), which show notable diversity. An attempt is made to resituate assemblages without clear spatial provenience into the framework established by studies of the material from in situ sediments containing bifacial elements from Verpillière II, with reference to the notes of former excavators of Verpillière I. Asymmetrically bifacially backed knives from Verpillière I derive from the entrance of the rock shelter. Moreover, despite distinctive differences of both sites and their bifacial assemblages, they share similarities with regard to both production sequences and components.